Searching for Success Factors of Agritourism: The Case of Kleve County (Germany) - Bosmann Mirjam; Hospers Gert-Jan; Reiser Dirk (European Countryside, 2021)
Agritourism is increasing in popularity as more urban residents appreciate the slower paced rural environment and its authenticity. External influences (political crises and pandemics) have recently reduced mobility which makes agritourism an attractive alternative to former more distant holiday destinations. Agritourists are interested in working farms, local production and animal husbandry. Some European regions (e.g., Bavaria and South Tyrol) have successfully developed agritourism whereas the majority of rural regions are left behind. Agritourism diversifies farmers’ business model and increases their income. For our study, we chose Kleve County (Lower Rhine Area, Germany) as an exemplary region for a touristically unknown rural area. Regional opinion leaders, farmers and industry experts were interviewed to share their experiences about factors that could further and contribute to successful development of agritourism. The results of our case study and supplementary market interviews suggest that its success in less known rural regions depends on the geographic location, mutual efforts of local visionary entrepreneurs, regional beneficial networks and on committed political stakeholders to develop a sustainable business model. The results may be useful for other comparable European rural regions to diversify their farming and develop their own business model.